Religion and conflict attribution: an empirical study in the religious meaning system of Christian, Muslim and Hindu students in Tamil Nadu, India - Anthony, Francis-Vincent (Radboud studies in humanities, 2014)
Religion in a pluralistic society can play a dual role with regard to conflict. It can promote either violence or peace. Religion and Conflict Attribution examines the causes of interreligious conflict as perceived by Christian, Muslim and Hindu college students in Tamil Nadu, India